Study on the Molecular Mechanism of Antioxidant Health Effect of Tuna Dark Meat Enzymatic Polypeptides - Diya, Zhang; Xin, Dong; Chunyu, Guo (Archives of Surgery and Clinical Research, 2024)
In order to study the molecular mechanism of the antioxidant effect of enzymatically hydrolyzed tuna dark meat peptides, this article uses alkaline protease to enzymatically hydrolyze tuna dark meat, and at the same time performs peptide sequencing using matrix-assisted laser dissociation time-of-flight mass spectrometry (MALDI TOF/TOF). Discovery Studio (DS) performed molecular docking. Finally, the antioxidant effect was verified through DPPH clearance experiments. The results show that the dominant peptide sequences in the tuna dark meat hydrolyzed polypeptides are LAPGQ, GGGDPI, and PLRLP; through molecular simulation methods (Discover Studio, DS), the potential target of the above-mentioned enzymatic polypeptides was screened out to be Keap1, thus predicting antioxidant activity. It provides theoretical support for further research on enzymatic peptides. Through DPPH clearance experiments, it was found that both the enzymatic hydrolysate and LAPGQ, GGGDPI, and PLRLP have antioxidant activity, confirming their effects.